Effectiveness of a nursing intervention to diminish preoperative anxiety in patients programmed for knee replacement surgery: Preventive controlled and randomized clinical trial - Medina Garzón, Mauricio (Investigación y Educación en Enfermería, 2019)
Objective. This work was conducted to determine the effectiveness of a nursing intervention, based on the motivational interview, to diminish preoperative anxiety in patients programmed for knee replacement surgery. Methods. Preventive type controlled and randomized clinical trial, on a sample of 56 patients programmed for knee replacement surgery in a clinic in Girardot (Colombia). Random assignment was made: an intervention group (n=28) and a control group (n=28). The six-question Amsterdam Preoperative Anxiety and Information Scale was applied before and after the intervention. The scale has a total score ranging from 5 to 30; the higher the score, the greater the preoperative anxiety. The nursing intervention was conducted in three sessions of motivational interview each lasting 40 min, during the six weeks prior to the surgical procedure; the control group received conventional management of education in the health institution. Results. The mean score of preoperative anxiety was equal in the pre-intervention evaluation in both groups (19.76 in the experimental versus 22.02 in the control =22.02; p<0.226), while during the post-intervention, the anxiety score was lower in the intervention group compared with the control group (15.56 and 20.30, respectively; p<0.013). Conclusion. Nursing intervention based on the motivational interview was effective in diminishing preoperative anxiety in patients programmed for knee replacement surgery. How to cite this article: Cómo citar este artículo: Medina-Garzón M. Medina-Garzón M. Effectiveness of a Nursing Intervention to Diminish Preoperative Anxiety in Patients Programmed for Knee Replacement Surgery: Preventive Controlled and Randomized Clinical Trial. Invest. Educ. Enferm. 2019; 37(2):e07.